Evaluation Criteria of Innovative Capacity of Interprises through Capacity of Technology - Phuong, Trang Vu; Tien Anh, Tran (VNU Journal of Science: Policy and Management Studies; Vol 35 No 1DO - 10.25073/2588-1116/vnupam.4170, 2019)
Abstract : In the industrial revolution 4.0 context, the assessment of the enterprise's innovation capacity can be considered at the base of the assessment of the technological capacity for the enterprise's production activities. The results are based on the methodology of reviewing materials focusing on human capacity in the chain of operations from the selection of technology according to the capacity and the ability to use and develop technology. The paper concludes with a recommendation for a set of criteria for technology capability assessment, namely (1) technology searching capability; (2) technology receiving capability; (3) technology operating capability; (4) innovation capability; and (5) technology innovating capability. Keywords: Evaluation Criteria,  Innovative Capacity, Technological capabilities.